Evaluation of Anti-diabetic Drugs using ATC/DDD and DU90% Methods in Diabetes Mellitus Patients: Evaluasi Obat Antidiabetik menggunakan Metode ATC/DDD dan DU90% pada Pasien Diabetes Melitus - Hendra, Godeliva Adriani; Nugraha, Dhanang Prawira; Krisdia, Tuswatul Anggi (Universitas Tadulako, 2024)
Background: Diabetes Mellitus (DM), which results from insulin resistance, is closely linked to long-term damage to pancreatic beta cells, organ dysfunction, and organ failure, particularly in the eyes, kidneys, nerves, heart, and blood vessels. The development of the ATC/DDD system is necessary to increase global drug knowledge, ensure equitable drug availability, and promote responsible drug use. Objectives: This study aimed to identify data on patient characteristics and oral anti-diabetic drugs and insulin using the ATC/DDD and DU90% methods. Material and Methods: This study was a cross-sectional evaluation of oral anti-diabetic medications and insulin using the ATC/DDD method and DU90% at the Bala Keselamatan Bokor Turen Hospital from January to December 2022. The inclusion criteria were patients diagnosed with type 1 or type 2 diabetes mellitus, with or without comorbidities, who were treated with oral anti-diabetic medications and a combination of insulin and oral medications. In the present study, the incomplete medical record data served as the exclusion criteria. The sample for this investigation consisted of 238 patients selected using the complete sampling technique. Results: Most patients who used oral anti-diabetic medications and insulin were between the ages of 46 and 65 (71.34%), were female (73.2%), had standard body mass index (BMIs between 18.5 and 25), and had diagnoses of DM + HT (20.73%) and Type II DM (18.29%). Glulisin was the most used anti-diabetic drug, accounting for 589 DDD/100 days of hospitalization, and DU90% was 21.39%. Conclusion: Glulisin is the most frequently prescribed anti-diabetic medication at Bokor Turen Hospital.